Resistant starch from underutilised legumes as prebiotic and its effect on the growth of Danio rerio and Lates calcarifer - Chiew, Ivan Kar Mun (2018)
Aquaculture is an important protein source for Malaysia. However, the susceptibility of fish to disease leads to heavy losses and hinders production. A potential solution is the supplementation of diets with prebiotics: non-digestible carbohydrates which improve growth and health by modulating gut microbiota to favour beneficial bacteria. Resistant starch (RS) is a prebiotic commonly fed to terrestrial animals, but little work has been performed on aquatic animals. Therefore, this study investigated the use of RS isolated from underutilized crops as a prebiotic in fish. Six species of underutilised legumes (adzuki beans, mung beans, black-eyed peas, pigeon peas, Bambara groundnuts and red lentils) were used for starch isolation via alkaline steeping, followed by processing involving enzyme or acid hydrolysis, and lastly gelatinisation and retrogradation to increase RS yield. Starch was isolated with yields of 25 – 40%, while enzyme hydrolysis pre-treatment was more effective and improved RS content up to 18.06% in most legumes. The starch and RS samples were then supplemented at 5% (w/v) in nutrient broth to investigate their prebiotic effect on fish gastrointestinal lactic acid bacteria. Enzyme pre-treatment improved the growth of W. cibaria, L. garvieae and E. gilvus by up to 43.9% for most legumes tested. Red lentil and adzuki bean enzyme-RS showed highest prebiotic potential and was applied in the zebrafish growth trial, while only red lentil was used in the Asian sea bass growth trial. Supplementation of diets with RS from legumes provided no significant difference in the growth and performance parameters measured in both zebrafish and Asian sea bass when supplemented at 2.5% and fed for five and six weeks respectively. Further studies involving analysis of immune parameters is necessary to identify prebiotic potential on targeted fish. Nevertheless, this study contributed to promote future work in using underutilised legumes as prebiotic source to improve the fish health under commercial conditions of rearing.